JAK–STAT signaling pathway in the pathogenesis of atopic dermatitis: An updated review - Huang, I-Hsin; Chung, Wen-Hung; Wu, Po-Chien; Chen, Chun-Bing (Frontiers in Immunology, 2022)
Atopic dermatitis (AD) is a chronic, inflammatory, pruritic form of dermatosis with heterogeneous manifestations that can substantially affect patient quality of life. AD has a complex pathogenesis, making treatment challenging for dermatologists. The Janus kinase (JAK)–signal transducer and activator of transcription (STAT) pathway plays a central role in modulating multiple immune axes involved in the immunopathogenesis of AD. In particular, Th2 cytokines, including interleukin (IL)-4, IL-5, IL-13, IL-31, and thymic stromal lymphopoietin, which contribute to the symptoms of chronic inflammation and pruritus in AD, are mediated by JAK–STAT signal transduction. Furthermore, JAK–STAT is involved in the regulation of the epidermal barrier and the modulation of peripheral nerves related to the transduction of pruritus. Targeting the JAK–STAT pathway may attenuate these signals and show clinical efficacy through the suppression of various immune pathways associated with AD. Topical and oral JAK inhibitors with variable selectivity have emerged as promising therapeutic options for AD. Notably, topical ruxolitinib, and systemic upadacitinib, and oral abrocitinib were approved by the U.S. Food and Drug Administration for treating patients with AD. Accordingly, the present study reviewed the role of JAK–STAT pathways in the pathogenesis of AD and explored updated applications of JAK inhibitors in treating AD.